E-COMMERCE ADOPTION AS A COMPETITIVE CATALYST FOR MSMES: INSIGHTS FROM DIGITAL TRANSFORMATION IN EMERGING ECONOMIES - Meilisa Meilisa; Hefrizal Handra; Hafiz Rahman; Febriandi Prima Putra (Jurusan Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Mataram, 2026)
This study investigates e-commerce adoption among Micro, Small, and Medium Enterprises (MSMEs) in emerging countries like Indonesia, where urban centers are rapidly expanding and digital economies are growing. Using Pekanbaru City as a case study, the research highlights persistent challenges that hinder e-commerce growth in these markets. A Technology-Organization-Environment (TOE) framework is developed to identify key factors influencing MSMEs’ decisions to adopt e-commerce platforms. The study analyzes variables including human resources and organizational awareness, compatibility and relative advantage, as well as market pressure, digital readiness, and government support. Primary data from 110 MSMEs in Pekanbaru were collected through questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Findings show that relative advantage, human resource capacity, and government support significantly affect e-commerce adoption, while compatibility, awareness, and market readiness do not. These insights offer theoretical and practical guidance for policymakers and business leaders aiming to accelerate digital transformation. Ultimately, the study presents a policy framework to promote sustainable and equitable economic growth by enabling MSMEs in developing urban areas to adopt digital technologies effectively.